2017
DOI: 10.1089/lrb.2017.0022
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors in Chronic Edema: A Case–Control Study

Abstract: Objective: To examine psychological health and perceived social support in patients with chronic oedema (CO).Methods: A random sample of patients who had been previously identified within a chronic oedema (CO) service in an urban area of south west London were group matched for age and gender with community controls in a case control study. Results:One hundred and seven cases and 102 controls (women 82%) were identified. CO was caused by cancer or its treatment in 51 (48%) of cases and affected the leg in 65 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…As for edema, research in the United Kingdom has shown an association between chronic edema and quality of life, which is particularly reduced in terms of physical and emotional capacity and health in general (30) . It is considered that educational activities that favor self-care can positively impact the reduction of edema and improve HRQoL.…”
Section: Although the Relationship Between Depressionmentioning
confidence: 99%
“…As for edema, research in the United Kingdom has shown an association between chronic edema and quality of life, which is particularly reduced in terms of physical and emotional capacity and health in general (30) . It is considered that educational activities that favor self-care can positively impact the reduction of edema and improve HRQoL.…”
Section: Although the Relationship Between Depressionmentioning
confidence: 99%
“…Traditional individual approaches to learning should be challenged, and approaches that draw children, parents, and professionals together may be beneficial and inform the development of new therapeutic approaches. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…Lymphedema management (CDT) is typical of many conditions developed in an era when an acute illness model still predominated, and concepts and structures continue to influence the way in which care is approached. 18,19 Lymphedema may be defined as a chronic disease, however, treatment with CDT is based more on an acute model of care with interventions delivered during acute exacerbations. This may influence the ineffectiveness of health care systems designed to treat acute disease rather than chronic disease.…”
Section: Discussionmentioning
confidence: 99%